Molecular and Physiological Mechanisms of Antenatal Exercise for Preventing Hypertensive Disorders in Pregnancy: A Systematic Review - Ayu Mei Wulandari; Savira Oktavia Ainiyati (Faculty of Medicine, Universitas Negeri Surabaya, 2025)
Hypertensive Disorders in Pregnancy (HDP) is a complex vascular complication associated with impaired placental angiogenesis and endothelial dysfunction. Globally, HDP represents a significant cause of adverse outcomes for both mothers and newborns. This systematic review aims to explore the molecular and physiological mechanisms contributing to the prevention of HDP through antenatal exercise. Research articles published between 2015 and 2025 were systematically identified from PubMed, ScienceDirect, and Google Scholar databases, resulting in 10 studies meeting the inclusion criteria. Findings indicate that regular exercise during pregnancy improves endothelial function, balances angiogenic activity, and reduces oxidative stress and inflammation. Molecular mechanisms include increases in vascular endothelial growth factor (VEGF) and nitric oxide (NO), as well as decreases in inflammatory markers. This supports improved placental perfusion and decreased vascular resistance, leading to lower systolic and diastolic blood pressure. This review concludes that antenatal exercise provides multifactorial protection through physiological and molecular pathways, potentially becoming a safe, accessible, and affordable non-pharmacological strategy to mitigate HDP risk and promote maternal health.